If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3r + 8)(3r + -8) = 0 Reorder the terms: (8 + 3r)(3r + -8) = 0 Reorder the terms: (8 + 3r)(-8 + 3r) = 0 Multiply (8 + 3r) * (-8 + 3r) (8(-8 + 3r) + 3r * (-8 + 3r)) = 0 ((-8 * 8 + 3r * 8) + 3r * (-8 + 3r)) = 0 ((-64 + 24r) + 3r * (-8 + 3r)) = 0 (-64 + 24r + (-8 * 3r + 3r * 3r)) = 0 (-64 + 24r + (-24r + 9r2)) = 0 Combine like terms: 24r + -24r = 0 (-64 + 0 + 9r2) = 0 (-64 + 9r2) = 0 Solving -64 + 9r2 = 0 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '64' to each side of the equation. -64 + 64 + 9r2 = 0 + 64 Combine like terms: -64 + 64 = 0 0 + 9r2 = 0 + 64 9r2 = 0 + 64 Combine like terms: 0 + 64 = 64 9r2 = 64 Divide each side by '9'. r2 = 7.111111111 Simplifying r2 = 7.111111111 Take the square root of each side: r = {-2.666666667, 2.666666667}
| 2x^2-7=59 | | 7y=-4x | | 2(x+4)+2=8x+2(x+2) | | (7x+84)=112 | | 3x+2x-2=4x+x+2 | | -0.2-q=9q | | X*.05833333333=(X-113) | | N^7/10 | | 2g+3G=10 | | 4(-y+2)=-1 | | X/3=70 | | N^10/7 | | 2m+-3m-8=26 | | Px+Q=X+1 | | 2x+4(2x+8)=10x+32 | | 1+8x^2+x^4= | | 90=(4x+12)+(6x+8) | | 4In(2x+3)=11 | | .15x+x=97.75 | | 4m+m=-90 | | (x+12)(x-7)=0 | | [8x]=28 | | .25(x+4)=41 | | 7/6=x/5 | | (7/28)=(3/x) | | 3x+24=4-10 | | 3(a+1)=5(a-1) | | x^3-2x^2-09+18=0 | | -112/16 | | 5x(3x-5)(x+1)=0 | | y=e^2x+17 | | Y=2x+a |